Catalog of type specimens of the fish collection of the Núcleo de Pesquisas em Limnologia, Ictiologia e Aquicultura (NUP), Universidade Estadual de Maringá, Paraná, Brazil - de Oliveira, Rianne C.; Ota, Renata R.; Deprá, Gabriel C.; Zawadzki, Cláudio H.; Pavanelli, Carla S.; Graça, Weferson J. Da (Zootaxa, 2022)
This study aims to provide an annotated list of the type-material housed in the fish collection of the Núcleo de Pesquisas em Limnologia, Ictiologia e Aquicultura (NUP), Universidade Estadual de Maringá, Paraná, Brazil. NUP’s fish type collection hosts type-material of 157 species, distributed in 503 lots (11 holotypes and 492 lots of paratypes) totalling 2,915 specimens. For each species, catalog numbers of all available lots are provided, and for each lot, total number of specimens, range of variation of standard length, number of cleared and stained specimens (when any), locality data, collectors, and date of collection, are provided.